Mainstreaming gender sensitivity in cash crop market supply chains: The role of CSR in Nigeria's oil producing communities - Joseph Ikechukwu Uduji; Elda Nduka Okolo-Obasi; Justitia Odinakachukwu Nnabuko; Geraldine Egondu Ugwuonah; Josaphat Uchechukwu Joe Onwumere (African Governance and Development Institute (AGDI), 2024)
Purpose -The purpose of this paper is to critically examine the multinational oil companies' (MOCs) corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of the global memorandum of understanding (GMoU) on mainstreaming gender sensitivity in cash crop market supply chains in the Niger Delta region of Nigeria. Design/ methodology/ approach - This paper adopts an explanatory research design, with a mixed method to answer the research questions and test the hypotheses. A total of 1200 rural women respondents were sampled across the Niger Delta region. Findings - Results from the use of a combined logit model and propensity score matching indicate a significant relationship between GMoU model and mainstreaming gender sensitivity in cash crop market supply chains in the Niger Delta. Research limitations/implications - This study implies that MOCs' CSR intervention that improve women's access to land and encourage better integration of food markets through improved roads and increased mobile networks, would enable women to engage in cash crop production. Originality/ value - This research contributes to gender debate in agricultural value chain from a CSR perspective in developing countries and rational for demands for social projects by host communities. It concludes that business has an obligation to help in solving problems of public concern.
Keywords: 330; Gender; cash crop market; supply chains; corporate social responsibility; multinational oil companies; sub-Saharan Africa